Review of fruit rot diseases of important tropical and some temperate fruit crops - Abd Murad, Nur Baiti; Mohd Zainudin, Nur Ain Izzati (Universiti Putra Malaysia Press, 2017)
Fruit rot is a common disease that affects the quality and quantity of the produced fruits. It may happened during pre-harvest stage and usually the condition of the fruits will become worse at postharvest stage if there are no any precautions taken during the picking, storing, packaging and transporting processes. The disease is mainly caused by the infection of fungi supported by a conducive condition like susceptible hosts, relative humidity and unsuitable temperature, besides other microorganisms such as bacteria, viruses and nematodes. The infection may arise from soilborne, waterborne, wind borne and insects bite transmission. Fruit rot diseases have been reported to cause by many fungal species such as Fusarium species, Alternaria species, Lasiodiplodia species, Aspergillus species, Penicillium species, Colletotrichum species and Botrytis species. This review will provide sufficient information about rot diseases on fruit, fungal species that cause the diseases, effective control methods and managements as well as economic losses and health issues related to the diseases.